EFFECT OF WORK ENVIRONMENT, EMPLOYMENT MOTIVATION, WORK STRESS ON EMPLOYEES PERFORMANCE PT.ADIRA FINANCE SOLO - L, Andreas Utomo; Hariyanti, Hariyanti (KELOLA, 2018)
The purpose of this study is to determine the effect of work environment, work motivation and work stress on employee performance PT.Adira Finance Solo. The sample of this research is 100 respondents. Data analysis tool with: instrument test, classic ausmsi test, multiple linear regression analysis, t test, F test and R2 test. The result of regression analysis shows that work environment, work motivation and work stress have a positive effect on employee performance. Result of t test shows that: Work motivation and work stress have no significant effect on employee performance, while work environment has significant effect to employee performance. F test results show together - the variables work environment, work motivation, and work stress have no significant effect on teacher performance. Test Results Coefficient of determination (R2) of the value Adjusted R Square obtained results of 0.167 which means Performance of employees of PT. Adira Finance Solo can be explained by work environment, work motivation and work stress, by 16.7%, while the remaining 83.3% is explained by other variables not included in the research. For example communication, commitment, work discipline.Keywords: Work Environment, Work Motivation and Job Stress